Development of Central Venous Stenosis Upon ICD Implantation in Dialysis Patients: A Non-Negligible Issue - Timal, Rohit J; Karalis, Ioannis; Cabezas, Jose M Montero; Rotmans, Joris I; Hensen, Liselotte C R; Buiten, Maurits S.; Bie, Mihaly K de; Erven, Lieselot van; Putter, Hein; Schalij, Martin J.; et al. (Cardiology and Cardiovascular Medicine, 2022)
Background: In hemodialysis patients, implantable cardioverter-defibrillator (ICD) implantation may result in central venous stenosis (CVS) with associated symptoms, such as pain, edema of the ipsilateral arm, facial edema, and loss of dialysis access. However, literature concerning CVS in dialysis patients with a cardiac implantable electronic device is scarce. Methods: We conducted a prospective cohort study in which we investigated the incidence of CVS in end-stage renal disease patients on chronic dialysis who received an ICD as part of participation in the randomized ICD2 trial. A venography was performed before ICD implantation and at 1 year follow-up. Results Between 2007 and 2017, 80 patients on dialysis received an ICD according to ICD2 trial protocol. Our population mainly consisted of males (76.3%), and had a median age of 67 years. Hemodialysis was the predominant dialysis modality (71.3%). The ICD was implanted in the right pectoral region in 58 patients (72.5%). A minority of the patients (27.5%) had a history of central venous catheters use, ipsilateral to ICD implantation site. Median follow-up was 16 months (IQR 13–35). Prospective assessment of central vein patency was possible in 56 patients (70.0%). Partial obstruction of central vein at follow-up was present in 19 out of 56 patients (33.9%) and complete occlusion in 4 patients (7.1%). With a complete clinical follow-up of all patients with a median duration of 3.5 years (IQR 2.7 - 6.3), 3 patients developed clinically significant symptoms of CVS. Conclusions Development of CVS in patients on chronic dialysis who received an ICD is a cause of concern. Prevention of such complications deserves attention and further research.